Clark E. Cunningham’s Cutting-edge Contributions to Research on Biomedical Appropriation in Southeast Asia - Lorraine V. Aragon (Université de Provence, 2021)
Clark Edward Cunningham (1934-2020), professor emeritus at the University of Illinois (USA), pioneered the subfields of medical anthropology and biomedicine in Southeast Asia during the 1960s and 1970s. Cunningham’s contributions to the anthropology of Thailand and Indonesia on health, social structure, symbolism, and houses, emerged from decades of fieldwork. His exemplary teaching and research influences endure. Beyond biographical details and personal reflections by two former students (Lorraine V. Aragon and Susan O. Long), this two-part Memoriam essay highlights the foresight and insights of Cunningham’s 1970 Social Science and Medicine article titled “Thai Injection Doctors: Antibiotic Mediators.” Despite its brevity and twentieth-century style, the main points of this essay about a popular and semi-illicit mode of biomedical healing that entered the rural Thai marketplace hold up well fifty years after its publication.